XRPD and Rietveld refinement for Al5NdNi2 compound. Issue 2 (4th April 2018) - Li, Degui; Luo, Kun; He, Bing; Liang, Liuqing; Qin, Ming; Lu, Tian
Abstract : A new ternary compound Al5 NdNi2 was prepared by melting a stoichiometric mixture of aluminum, neodymium, and nickel in an arc furnace and annealing in vacuum. The crystal structure of Al5 NdNi2 was studied by X-ray powder diffraction technique and Rietveld analysis. All diffraction lines of Al5 NdNi2 were indexed, and the lattice parameters were refined with an orthorhombic structure type of space group Immm (No.71) using Rietveld analysis program DBWS-9807. The lattice parameters are presented, a = 7.0508(1) Å, b = 9.5690(1) Å, c = 3.9792(1) Å, V = 268.47 Å 3, Z = 2, ρ = 4.91 g cm −3, and RIR = 1.23.